Design strategy of concurrent multi‐band Doherty power amplifier. Issue 12 (1st September 2015) - Kalyan, Robin; Rawat, Karun; Koul, Shiban Kishan
Abstract : This paper proposes design methodologies of concurrent multi‐band Doherty power amplifiers (PAs) based on multi‐band impedance inverting networks and multi‐band phase offset lines (POLs). Design procedures for implementing such multi‐band impedance inverting networks and multi‐band POLs at arbitrary frequencies are presented here. For validating the design procedures, tri/quad‐band Doherty PAs are designed, fabricated and tested using continuous wave (CW) and modulated signals in discrete mode and concurrent mode. The tri‐band Doherty power amplifier (DPA) is implemented at 1600, 1900 and 2200 MHz. CW signal measurement of tri‐band DPA shows an efficiency of 46%, 40% and 42%, respectively, around 6 dB output power back‐off (OPBO). The quad‐band DPA is implemented at 1600, 1960, 2140 and 2350 MHz. Measured results using CW signal shows an efficiency of 40%, 37%, 30% and 31%, respectively, around 6 dB OPBO.